2013
DOI: 10.1007/s12011-012-9596-1
|View full text |Cite
|
Sign up to set email alerts
|

Trace Element, Antioxidant Activity, and Lipid Peroxidation Levels in Brain Cortex of Gerbils After Cerebral Ischemic Injury

Abstract: Proper trace element level and antioxidant enzyme activity are crucial for the brain in maintaining normal neurological functions. To our knowledge, alteration of lipid peroxidation status, trace element level, and antioxidant activity in the homogenates of brain cortex after cerebral ischemia in gerbil, however, has not been investigated so far. Male Mongolian gerbils were divided into control and ischemic subjects. Cerebral ischemia was induced by occlusion of the right middle cerebral artery and right commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 39 publications
2
58
0
3
Order By: Relevance
“…SelP−/−knockout mice display a neurological phenotype with subtle disruption of memory processes and spatial learning [60]. Moreover, other researchers have shown reduction in brain Se levels followed by a decrease in Se-dependent enzyme activity and impaired motor coordination in the same model [52,61,62]. Burk et al confirmed that the knock-out of SelP or apoER2 significantly depleted the brain's Se pool [63].…”
Section: Selenoprotein Pmentioning
confidence: 96%
See 2 more Smart Citations
“…SelP−/−knockout mice display a neurological phenotype with subtle disruption of memory processes and spatial learning [60]. Moreover, other researchers have shown reduction in brain Se levels followed by a decrease in Se-dependent enzyme activity and impaired motor coordination in the same model [52,61,62]. Burk et al confirmed that the knock-out of SelP or apoER2 significantly depleted the brain's Se pool [63].…”
Section: Selenoprotein Pmentioning
confidence: 96%
“…SelPs are an unusual family that can incorporate multiple Sec residues, while other selenoproteins can integrate only one. Therefore, SelP has been postulated as being involved in both Se intercellular transport and storage [52,53]. The N-terminal domain of SelP contains one Sec residue, while the other nine are located in the C-terminal.…”
Section: Selenoprotein Pmentioning
confidence: 99%
See 1 more Smart Citation
“…При окислительном стрессе, сопровождающим развитие инсульта, истощение Se с последующим снижением активности селензависимых фермен-тов является важным фактором этиопатогенеза этой патологии (Fang et al, 2013;Zangieva, 2013;Bhowmick et al, 2014;Loscalzo, 2014). Известно, что во время мозгового ишемического каскада фактором, который приводит к митохондриаль-ной дисфункции, является недостаток кислорода, сопровождающийся снижением продукции АТФ.…”
Section: Introductionunclassified
“…Trace element toxicity has also been attributed to their generation of ROS (Meharg and Hartley-Whitaker, 2002;Fang et al, 2013) that cause oxidative damage to biomolecules and eventual cell death (Gunes et al, 2007). Plants have evolved mechanisms to protect cells and subcellular systems from the effects of ROS (e.g.…”
Section: Introductionmentioning
confidence: 99%